Laparoscopic hysterectomy. Communication of a Series - Siu, Alejandro (2015)
Objective: To determine our experience with laparoscopic hysterectomy. Design: Patients from private hospitals, attended from January 1997 to December 1999. Material and Methods: Fifty patients were subjected to laparoscopic hysterectomy, uterine arteries were sectioned and in many cases the cardinal ligaments were partially sectioned as well. The uterus was removed vaginally. Results: Eighteen of them (36%) had previously received estrogen therapy. Average age was 43 year-old, 6 of them (12%) nulliparous, the remainder (88%) had had a previous pregnancy, with an average number of 3,5 gestations. Surgical indications were uterine myomata, benign ovarian cysts, adenomyosis, endometriosis, chronic pelvic pain, dysfunctional uterine bleeding and entero-pelvic adhesions. Anteroposterior colpoperineorraphy was done in 16 patients (32%). Average surgery time was 103 minutes. Uterine weight averaged 236 g. Among complications, we identified two urinary tract infections (4%), one dome infection, one vesical laceration (2%) in the patient whose uterus weighted 600 g, and one abdominal wall haematoma caused by trocar. Average hospital stay was 2,8 days. Conclusions: Comparing this technique with conventional hysterectomy, we have observed longer duration of surgery, but faster postoperative recuperation, shorter hospital stay, faster remission of pain and it was possible to remove the uterus vaginally in patients with a prolapsed uterus and strong pelvic adhesions.